Critical Thinking In Nursing: Unraveling The Layers Of Decision-Making (Journal of Namibian Studies : History Politics Culture, 2022)
Searching for, acquiring, assessing, analyzing, synthesizing, and conceptualizing information in order to enhance one's thinking with self-awareness and the capacity to use this knowledge by being creative and taking chances is the process of critical thinking. For a very long time, the nursing process has been crucial to nursing practice. In order to consider a plan of care as the cornerstone of professional practice in routine nursing practice, the nursing process has been utilized as a problem-solving exercise. A nursing care plan that offers students an educational opportunity to hone their critical thinking and decision-making abilities may be described by the nursing process. In nursing, the nursing process is viewed as a decision- making methodology that fosters critical thinking. The five stages of this procedure are diagnosis, planning, execution, assessment, and evaluation.